2007
DOI: 10.1111/j.1365-2427.2006.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblage patterns in the littoral zone of a European reservoir

Abstract: 1. Although reservoirs are common aquatic habitats in Europe, there is little quantitative information on the spatial organisation of fish assemblages inhabiting their littoral zones. Consequently, we characterised fish assemblage structure in the littoral zone of a reservoir (Lake Pareloup) in SW France during late spring, summer and early autumn (the growing season). 2. We measured the relative abundance of fish, weekly from mid-May to mid-October, using point abundance sampling by electrofishing. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 63 publications
(167 reference statements)
4
32
2
1
Order By: Relevance
“…These ecospecies dominated in the pelagic zone and mostly avoided the littoral during the day. The observed day avoidance of shallow areas by large fish agrees with other studies from lakes, rivers, or reservoirs (Duncan & Kubečka, 1995;Wolter & Freyhof, 2004;Romare et al, 2003;Brosse et al, 2007;Erös et al, 2008) and seems to be a very common trend in freshwater ecosystems. The pelagic zone is suggested to be a more advantageous zone for large fish species because, contrary to small fish, they face a lower risk of predation in this zone (Werner et al, 1983;Lammens et al, 1992).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These ecospecies dominated in the pelagic zone and mostly avoided the littoral during the day. The observed day avoidance of shallow areas by large fish agrees with other studies from lakes, rivers, or reservoirs (Duncan & Kubečka, 1995;Wolter & Freyhof, 2004;Romare et al, 2003;Brosse et al, 2007;Erös et al, 2008) and seems to be a very common trend in freshwater ecosystems. The pelagic zone is suggested to be a more advantageous zone for large fish species because, contrary to small fish, they face a lower risk of predation in this zone (Werner et al, 1983;Lammens et al, 1992).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, such sampling could also reveal the occurrence of potential predators and evaluate their impact on the diel distribution dynamics of different species and size categories. In European freshwaters, studies dealing with diel changes of fish distribution largely focused on only one species (Schulz & Berg, 1987;Zamora & Moreno-Amich, 2002;Jacobsen et al, 2004) or sampling of a community in only one zone (Brosse et al, 2007;Erös et al, 2008). However, there is a very limited number of studies that performed simultaneous quantitative sampling of the whole fish communities in both zones and periods (Wolter & Freyhof, 2004;Muška et al, 2013) and in our best knowledge there is no study providing picture of diel changes among all mentioned habitats simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks are known as well-adapted tools for dealing with such problems and to extract information out of complex, nonlinear data. These methods are more and more used for patterning assemblages (Worner and Gevrey, 2006;Brosse et al, 2007;de Thoisy et al, 2008) and predicting occurrence and/or abundance of various taxa (Gevrey et al, 2005;Leprieur et al, 2006). The aim of our study was first to pattern aquatic insect distribution so as to determine characteristic assemblages for the different sites and rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling was conducted on the day of full-moon in each month to avoid the influence of a lift net fishery where in lights used by fishermen during the new moon phase (Jutagate et al, 2003). Sampling was carried out in the littoral zone, as it is known to be the habitat preferred by larval fish (Brosse et al, 2007;Ríha et al, 2011). Maximum and mean depths of sampling sites were 1.07 and 0.48 m, respectively.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…The increased depth implies extensive flooding of terrestrial vegetation and could relate to production of prey resources for larvae (Quist et al, 2004). However, the plateau shape of relationships between water level and species richness as well as abundance indicated that the larval fish preferred the shallow littoral area rather than the deeper zone (Brosse et al, 2007).…”
Section: Patterns Of Larval Fish Assemblagesmentioning
confidence: 99%